Analisis Motivasi Belajar Peserta Didik Kelas X Mata Pelajaran Ekonomi di MA Muhammadiyah Nangahure - Mohamad Amir; Agustina Novaria (Journal on Education, 2023)
This study aims to find out how students' learning motivation in economics subjects at MA Muhammadiyah Nangahure. This is motivated by the low learning motivation of students in economics subjects which can be seen from the symptoms: There are still students who do not complete assignments given by the teacher, students who do not pay attention to the teacher when explaining subject matter, and students who do not dare to express opinions . This type of research is descriptive qualitative and the subjects are students and teachers. The object of this study was the learning motivation of the students and the informants consisted of 3 students as the main informants and 1 economics teacher as an additional informant. Data collection techniques in this study were observation, interviews, and documentation. The data analysis technique is descriptive statistical analysis of the presentation. Based on the results of the study it can be concluded that the learning motivation of students in economics subjects at MA Muhammadiyah Nangahure is already relatively high and overall the average learning motivation of students in economics subjects at MA Muhammadiyah Nangahure is at a high level of motivation but still when viewed from each -Each student himself is still not motivated in learning economics.